The Effect of Using Grammarly Apps on High School Students in Writing Recount Text Achievement: Pengaruh Penggunaan Aplikasi Grammarly terhadap Prestasi Menulis Teks Narasi Siswa Sekolah Menengah Atas - Masyitah Nurilla Mahdi; Wahyu Taufiq (Academia Open, 2025)
General Background The integration of digital and artificial intelligence technologies has become increasingly prominent in English language education, particularly to support writing development among learners of English as a Foreign Language. Specific Background Writing recount texts requires accurate grammar control, especially the simple past tense, which remains a persistent difficulty for vocational high school students. Knowledge Gap While previous studies on Grammarly mainly focus on senior high schools and universities, evidence from vocational school contexts is still limited. Aims This study aimed to examine whether the use of the Grammarly application contributes to students’ achievement in writing recount texts. Results Using a quasi-experimental pre-test–post-test control group design with 28 students in each group, the experimental class obtained a higher post-test mean score (87.86) than the control class (80.54), with a statistically significant difference (t = 3.337, p = 0.002), alongside a positive gain score and reduced score dispersion. Novelty The study provides empirical data from an underrepresented vocational education setting and demonstrates structured integration of automated feedback with guided revision practices. Implications The findings indicate that AI-based proofreading tools can be systematically incorporated into EFL writing instruction to support grammatical accuracy and more consistent learner performance 212506,+newartikel+ilmiah+masyi… . Keywords : Grammarly, Recount Text Writing, Vocational EFL Students, Grammar Accuracy, Quasi Experimental Design Key Findings Highlights: Experimental group obtained higher mean outcomes than the conventional class Score variation decreased indicating more uniform learner progress Automated feedback combined with revision practice supported error correction